DOT1L inhibitor improves early development of porcine somatic cell nuclear transfer embryos. - Jia Tao; Yu Zhang; Xiaoyuan Zuo; Renyun Hong; Hui Li; Xing Liu; Weiping Huang; Zubing Cao; Yunhai Zhang (PLoS ONE)
Incomplete epigenetic reprogramming of the genome of donor cells causes poor early and full-term developmental efficiency of somatic cell nuclear transfer (SCNT) embryos. Previous research indicate that inhibition of the histone H3 K79 methyltransferase DOT1L, using a selective pharmacological inhibitor EPZ004777 (EPZ), significantly improved reprogramming efficiency during the generation of mouse induced pluripotent stem cells. However, the roles of DOT1L in porcine nuclear transfer-mediated cellular reprogramming are not yet known. Here we showed that DOT1L inhibition via 0.5 nM EPZ treatment for 12 or 24 h significantly enhanced the blastocyst rate of SCNT embryos and dramatically reduced the level of H3K79me2 during SCNT 1-cell embryonic development. Additionally, H3K79me2 level in the EPZ-treated SCNT embryos was similar to that in in vitro fertilized embryos, suggesting that DOT1L-mediated H3K79me2 is a reprogramming barrier to early development of porcine SCNT embryos. qRT-PCR analysis further demonstrated that DOT1L inactivation did not change the expression levels of DOT1L itself but increased the expression levels of POU5F1, LIN28, SOX2, CDX2 and GATA4 associated with pluripotency and early cell differentiation. In conclusion, DOT1L inhibitor improved early developmental efficiency of porcine SCNT embryos probably via inducing the increased expression of genes important for pluripotency and lineage specification.